THE IMPACT OF EXTRINSIC AND INTRINSIC MOTIVATIONAL FACTORS TO STUDENT PERFORMANCE - Patulak, Angelina R.; Saerang, David P. E.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Human resources as one of the resources that exist in an organization plays an important role in the success of achieving the goals of the organization. A good quality of human resources can be seen from their development while studying. Motivation as a driver to meet aspects in producing good quality human resources by increasing student performance. Motivation have two factors which are external motivation that driven from outside such as peer acceptance, power motivation, fear of failure and authority expectations and internal motivation that driven within such as the need for achievement and to mastery goals. The purpose of this research is to determine the impact of Extrinsic and Intrinsic Motivational Factors To Student Performance. This research was classified as a quantitative research using Multiple Linear Regression method to testing the hypothesis of this research. The sampling techniques of this research was simple random sampling and use questionnaire to get the data with the sample size of 100 respondents. This research shows that partially and simultaneously Extrinsic and Intrinsic Motivational Factors have an impact to Student Performance with the result of fcount 24.550 larger than ftable and tcount of all variable larger than ttable.Â Keywords: Student Performance, Extrinsic Motivation, Intrinsic Motivation